Investigation on the Influences of STEAM-Based Curriculum on Scientific Creativity of Elementary School Students - Tran, Ngoc-Huy; Huang, Chin-Fei; Hsiao, Kuo-Hung; Lin, Kuan-Li; Hung, Jeng-Fung (Frontiers in Education, 2021)
Up until now, there have been several different viewpoints on creativity in general and creativity in the science field in particular. Furthermore, STEAM (science, technology, engineering, arts, and mathematics) education is increasingly successful and widespread around the world; however, few studies on its impact on scientific creativity exist. As a result, research on the influence of STEAM-based curriculum on students’ scientific creativity is critical. Elementary school students were chosen to be investigated in this research, and the main topic of the STEAM-based curriculum was about a house-shaped money-saving tube with the concept of lock science, which was developed and created by the authors’ team. This research produced two phases of courses: Lock Science Courses (2 weeks) and STEAM-based courses (2 weeks). In this study, sixty-six elementary students from two separate courses were divided into two groups: control and experimental. This research used a counterbalanced design. The control group took Lock Science Courses first and then STEAM-based courses, while the experimental group did the opposite. As a pretest and posttest, students in both groups were asked to complete the “scientific creativity test” (Cronbach’s α, 0.87). The findings of the paired t-test study indicate that both the control and experimental groups have shown significant improvement in their scientific creativity. However, only the fluency and flexibility components of scientific creativity (consisting of fluency, flexibility, and originality) showed considerable development, whereas the originality component remained unchanged. This research also found that after engaging in a STEAM-based curriculum, there was no substantial difference in scientific creativity between males and females. Further discussion is provided.